Reviving from the Pandemic: Strategies for Travel and Tourism Industry - , Prakashkumar Hasmukhbhai Patel, Baxis Patel, Stuti Trivedi, Dilip Rasiklal Vahoniya (Archives of Current Research International, 2025)
Introduction: Travel restrictions due to the COVID-19 outbreak in India, types of public transportation and tourist visas are being suspended and hence India will lose tourists from various states of India as well as from other countries. The research aim is to measure the change in travellers’ preference and expectations due to COVID-19 pandemic in the state of Gujarat and to provide strategies for reviving the travel and tourism industry. Methods: A total of 1043 travellers from Gujarat state were selected by non-probability convenient sampling method. Data were collected by online survey through a structured questionnaire during the pandemic era. Inferential statistical tools were used to infer the data collected for its Significance. Results: Data revealed the changes in travel plan, travelling duration, preferred mode of transportation and convoys’ prefer during travelling. On the other hand significant impact has been found on travel plans due to the COVID-19 outbreak. Discussion: This study will help to entire links of travels to make proper strategies to cope with the challenges that the tourism sector is facing due to the COVID-19 outbreak. Executing strategies recommended in this research will help to reduce the pandemic's troublesome effects on the travel industry and it will help in building an environment that will make it simpler for travellers coming from India and from other countries.